THE IMPACT OF LONG TERM RELATIONSHIP, PROCESS INTEGRATION, COOPERATION ON SUPPLY CHAIN MANAGEMENT PERFORMANCE AND COMPETITIVE ADVANTAGE - AFRILIYANI, UCI; SUNARKO, BAMBANG (JOURNAL OF RESEARCH IN MANAGEMENT, 2019)
This research is conducted on Small and Medium Industries of Gumelem Coconut Sugarlocated in Gumelem, Susukan Subdistrict, Banjarnegara Regency. This study takes the title:"The Influence of Long Term Relationship, Process Integration, Cooperation on SupplyChain Management Performance and Its Impact on Competitive Advantage (Study onGumMem Coconut Sugar IKM)". The purpose of this study was to determine the effect oflong term relationships, process integration, cooperation on supply chain managementperformance and its effect on competitive advantage. The population in this study were allsmall and medium-sized industries of coconut sugar gumelem in Gumelem Kulon. Thenumber of respondents taken in this study were 71 respondents. Sample Randon Samplingis used in determining this respondent. Based on the results of research and analysis ofdata using Multiple Regression Analysis and Simple Regression Analysis shows that: (1)Long term relationships have a positive effect on supply chain management performance,(2) Process integration has a positive effect on supply chain management performance, (3)Cooperation has an effect positive for supply chain management performance, (4) Supplychain management performance has a positive effect on competitive advantage. Theimplications of the above conclusions are in an effort to increase customer satisfaction, theproducers should pay attention to various policies relating to long term relationships,process integration, cooperation. The efforts made are to improve the supply chainmanagement performance in full in accordance with the needs, policies, trust, cooperationrelated to customer satisfaction of coconut sugar gumelem. And also in order to maintaintight competition in the industrial world, companies must improve supply chain managementperformance.